Literasi Digital Untuk Peningkatan Kompetensi Guru Di Era Revolusi Industri 4.0 - Nafilatur Rohmah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Revolution of industrial 4.0 is requires education to meet. so that education can meet the needs of human resources in the future. The digitization of the education system requires teachers to have additional competencies namely digital competencies. Digital literacy for teachers is a necessity in using information and communication technology to assist teachers in carrying out effective and efficient teacher tasks. Strengthening digital literacy can be done for teachers by explaining, by use of information and communication technology in helping to carry out tasks as a teacher among others, by use of digital technology as an additional source of learning, by use of digital technology-based learning media, the provision of rapid information, school promotion, connecting to students, as well as the publication of work and information. In practice, strengthening digital literacy can be done in the form of training.